Correction: Psychosocial and sociodemographic factors associated with gestational blood glucose levels in women attending public hospitals: Results from baseline of MAASTHI cohort. - Prafulla Shriyan; Srinidhi Koya; Eunice Lobo; Onno Cp van Schayck; Giridhara R Babu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0293414.].